2020
DOI: 10.1177/1758835920928635
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular density assessed by CD31 predicts clinical benefit upon bevacizumab treatment in metastatic colorectal cancer: results of the PassionATE study, a translational prospective Phase II study of capecitabine and irinotecan plus bevacizumab followed by capecitabine and oxaliplatin plus bevacizumab or the reverse sequence in patients in mCRC

Abstract: Background: Targeted therapies offer novel opportunities to explore biomarkers based on their mode of action. Taking this into consideration, we evaluated six angiogenesis-related proteins as potential predictive biomarkers, which expression might predict the benefit of bevacizumab treatment in patients with metastatic colorectal cancer (mCRC). Methods: This was a phase II multicenter, two-armed, randomized study, in which patients with mCRC were treated with XELIRI (capecitabine and irinotecan) plus bevacizum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…We found that the vascular densities assessed by CD31 immunochemical intensities ( Bianconi et al, 2020 ) were significantly higher in the anterior horn and lower in the dorsal horn in CSM rats compared with those in the sham rats ( t -test, P < 0.001) ( Figures 9A,B ). To determine the angiogenic activity, we performed IHC with angiogenic markers including vWF and VEGF ( Starke et al, 2011 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We found that the vascular densities assessed by CD31 immunochemical intensities ( Bianconi et al, 2020 ) were significantly higher in the anterior horn and lower in the dorsal horn in CSM rats compared with those in the sham rats ( t -test, P < 0.001) ( Figures 9A,B ). To determine the angiogenic activity, we performed IHC with angiogenic markers including vWF and VEGF ( Starke et al, 2011 ).…”
Section: Resultsmentioning
confidence: 92%
“…The current study further investigated the distribution of CD31, VEGF and vWF expression in the anterior and posterior parts of the spinal cord after chronic compression. The CD31 immunostaining has been frequently used to assess the vascular density ( Bianconi et al, 2020 ), while the VEGF and vWF have been reported as angiogenesis biomarkers in many diseases ( Starke et al, 2011 ). Apart from the overall vascular changes, microvascular density assessed by CD31 were significantly increased in the anterior horn but decreased in the dorsal horn, and angiogenesis marked by vWF and VEGF were increased only in anterior horns in chronically compressed spinal cords.…”
Section: Discussionmentioning
confidence: 99%
“…An electronic search was performed in five major databases, identifying a total of 728 articles. After duplicate removal ( n = 371), screening by title and abstract ( n = 174) and full-text screening ( n = 168), 15 eligible articles were finally included for data extraction and quantitative analysis [ 14 , 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Out of the 15 studies, six were conducted in CRC patients, eight in liver cancer patients (specifically six in HCC patients and two in CCA patients), and one was a pan-cancer study that included all the tumor types ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings have shown microvessel density (MVD) is positively correlated with invasion depth, lymph node and distant metastases, and TNM stage in CRC patients [ 25 ]. CD31, a sensitive and specific endothelial marker of MVD, has positive correlations with TNM stage and lymph node metastasis [ 26 ]. Meanwhile, VEGFA, a major proangiogenic factor, induces mitosis and regulates endothelial cell permeability.…”
Section: Discussionmentioning
confidence: 99%